Effect of β-endorphin and Cortisol on the PHA Stimulated Lymphoblastogenesis - Yang, In Myung (Korean J Intern Med, 1986)
The mechanism of immune suppression in a severely stressful condition is not known. Since the demonstration of β-endorphin receptor on the surface of the circulating lymphocyte, it was reported that β-endorphin could suppress PHA stimulated lymphoblastogenesis. Because the concentration of β-endorphin was supraphysiologically high, it is doubtful that β-endorphin can suppress the lymphoblastogenesis directly in vivo. We investigated the suppression of PHA stimulated lymphoblastogenesis by β-endorphin in vitro and the effect of β-endorphin in some conditions where β-endorphin increases in vivo. PHA induced lymphoblastogenesis of T lymphocyte was maximal at the concentration of 5 μg/ml. β-endorphin could not suppress the blastogenesis even at the highest concentration. In the five healthy men who received metyrapone the previous night, PHA stimulated blastogeneses were not significantly suppressed. In a patient with Nelson’s syndrome, the lymphoblastogenesis was suppressed at all concentrations of PHA. Cortisol significant suppressed the blastogenesis even at the concentration of 10 μg/dl and its suppressive effect was shown in dose dependant manner. Our results suggested that β-endorphin could not suppress the lymphoblastogenesis directly in vivo.